Analyzing Water Resources in the Arab World: The Next Economic Danger - Badis, Nabila; Zermane, Karim (Finance and Business Economies Review, 2022)
This study aims to clarify the limited water resources in the Arab world, and the characteristics that make them require great security. Studies conducted by specialized Arab and regional organizations have unanimously agreed that the Arab region will face a large water deficit in the future medium term. Therefore, we recommend that the current available water resources should be counted in terms of their sources, the volume of supply and demand for them, to determine the water gap, the search for the impact of government spending on water resources and the feasibility of water investments in the face of the increasing demand.